Syeikh Muhammad Sa'id's Tafsir Nur Al-Ihsan: An Intertextual Reading: (Tafsir Nur al-Ihsan oleh Syeikh Muhammad Sa'id: Suatu Bacaan Intertekstual) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2014)
Sheikh Muhammad Sa'id ibn Umar's Tafsir Nur al-Ihsan is the second Qur'anic interpretation produced in the Malay language, written in the 19th century CE after Tarjuman al-Mustafid. The main objective of this study is to identify the extent of the influence of the external sources in Tafsir Nur al-Ihsan. The method employed to analyse Tafsir Nur al-Ihsan is that of intertextuality, as developed by Mikhail Bakhtin and as described, developed and analysed by Julia Kristeva. In terms of the research methodology, this study was done using library research and field work with a subjective approach that is both descriptive and qualitative. The study finds that eleven texts influenced Tafsir Nur al-Ihsan: Tafsir al-Jalalyn, Tafsir al-Jamal, Tafsir al-Baydawi, Tafsir al-Khazin, Tafsir al-Baghawi, Tafsir al-Tabari, Tafsir al-Qurtubi, Tafsir al-Razi, Tafsir al-Nasafi, Tafsir Ibn Kathir, and Tafsir al-Tha'labi. The findings of this analysis also show that Tafsir Nur al-Ihsan is mostly influenced by Tafsir al-Jalalyn. The most frequent application of the intertextual method is a parallel reading.Keywords: dialogism, history, Tafsir Nur al-Ihsan, intertextual reading, intertextual principles